Biocontrol of Leafhopper Amrasca Biguttula Infesting Eggplants Using Entomopathogenic Fungi and Plant Extracts - Fayroz T. Lafta; Aqeel Alyousuf; Hayat M.R. Mahdi (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The efficiency of entomopathogenic fungi and plant extracts were evaluated against the leafhopper Amrasca biguttula infesting eggplant; the trials were conducted at the Agricultural station and the lab of College of Agriculture - University of Basrah during the growing season of 2023. At the lab, the treatments included fungal suspensions and filtrates of Beauveria bassiana and Trichoderma harzianum, as well as the plant extracts of neem leaves (Azadirachta indica) and castor leaves and seeds (Ricinus communis). The results of fungal suspensions showed no significant differences in adult mortality between B. bassiana and T. harzianum, with rates of 55.9% and 59.0%, respectively. Mortality increased over time, reaching 83.5% at the highest concentration (1×108 spores/ml) after 72 hours. The lowest rate of 28.4% was observed at a lower concentration (1×106 spores/ml) after 24 hours. Also, the fungal filtrates indicated that the highest mortality was 64.7% for B. bassiana at a 100% filtrate concentration after 72 hours. However, B. bassiana at 75% concentration recorded the lowest rate of 17.71% after 24 hours. No significant differences were noticed in the mortality of the insect among the treatments of neem, castor leaves, and castor seeds; the rates were 82.97%, 82.76%, and 85.45%, respectively. All plant extracts at concentrations of 1% and 0.5% achieved 90% mortality after 24, 48, and 72 hours. Under the greenhouse conditions, the treatments included fungal suspensions, and plant extracts (neem and castor leaves), with their mixtures compared to the positive control, pesticide Sivanto. Neem extract caused the highest mortality rate of 80.8%. However, castor leaf extract recorded the lowest mortality rate of 66.8%, compared to Sivanto, reaching 100% mortality after 21 days.